Good business : - Endris, John (Lexington, 2016)
Business is a complex network of people, decisions affect everything and every choice has an impact. Learning ethics theory is key to establishing healthy and productive partnerships at work and also at home. This workbook provides you with proven theory and interactive case studies so you can explore the boundaries of good business in a group or alone.